2007
DOI: 10.1016/j.bbrc.2007.03.180
|View full text |Cite
|
Sign up to set email alerts
|

PREDetector: A new tool to identify regulatory elements in bacterial genomes

Abstract: In the post-genomic area, the prediction of transcription factor regulons by position weight matrix-based programmes is a powerful approach to decipher biological pathways and to modelize regulatory networks in bacteria. The main difficulty once a regulon prediction is available is to estimate its reliability prior to start expensive experimental validations and therefore trying to find a way how to identify true positive hits from an endless list of potential target genes of a regulatory protein. Here we intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 11 publications
0
83
0
Order By: Relevance
“…At the same time, using the list of cre targets in B. subtilis reported by Fujita (22), we used the PREDetector software program (33) to identify an additional 14-bp sequence, cre chiB (ATAAAGC GTTTACA), which is similar to the cis-acting element cre, in the promoter of chiB in the genomic sequence of B. thuringiensis HD-789 (see Data Set S1 in the supplemental material). The cre chiB element overlaps the Ϫ35 box of the chiB promoter (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, using the list of cre targets in B. subtilis reported by Fujita (22), we used the PREDetector software program (33) to identify an additional 14-bp sequence, cre chiB (ATAAAGC GTTTACA), which is similar to the cis-acting element cre, in the promoter of chiB in the genomic sequence of B. thuringiensis HD-789 (see Data Set S1 in the supplemental material). The cre chiB element overlaps the Ϫ35 box of the chiB promoter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we found that nagA and nagP of Bti75 contain a 16-bp dre-like sequence within their upstream regions that is also directly repressed by YvoA Bt (data not shown). To identify further possible YvoA Bt binding sites in the genome of B. thuringiensis HD-789, we used the PREDetector software program (33) to identify corresponding16-bp dre-like sequence of nagA, nagP, and chiB. The data are listed in Data Set S2 in the supplemental material.…”
Section: Discussionmentioning
confidence: 99%
“…YvoA-binding sites upstream of nagP (dre nagP ; ATTGGTATAGATCACT) and upstream of the nagAB-yvoA locus (dre nagA ; GCTGGTCTAGATCACT) of B. subtilis were used to search similar sequences upstream of nagP and nagA orthologues in Bacillus species using the PREDetector software program (24). This list of 18 dre sites (see Table S1 in the supplemental material) was used to generate a position weight matrix (named NagR 2011) for NagR (YvoA) regulon prediction in Bacillus species.…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine the putative sequence of the SigK binding site, promoter sequences have been aligned using the AlignX program from VectorNTI (Invitrogen). Subsequently, this short alignment of similar sequences was used as a matrix to detect other putative binding sites in sequenced mycobacterial genomes using the programs PredictRegulon (34) and PREDetector (16).…”
mentioning
confidence: 99%